In vitro characterization of belinostat glucuronidation: demonstration of both UGT1A1 and UGT2B7 as the main contributing isozymes. (3rd April 2017) - Dong, Dong; Zhang, Tianpeng; Lu, Danyi; Liu, Jie; Wu, Baojian
Abstract: 1. Belinostat is a histone deacetylase inhibitor that has been approved for the treatment of peripheral T-cell lymphoma. This study aimed to identify the UDP-glucuronosyltransferase (UGT) enzymes responsible for belinostat glucuronidation through kinetic determination using recombinant enzymes with determined enzyme concentrations. 2. The rate of glucuronidation was determined by incubation of belinostat with enzyme preparations. Kinetic parameters such as Km and V max were derived by fitting an appropriate model to the glucuronidation data. The role of active UGT enzymes to belinostat metabolism was evaluated using inhibition experiments and activity correlation analyses. 3. Human liver microsomes generated a glucuronide metabolite (i.e. belinostat glucuronide) from belinostat. The glucuronide structure was confirmed by high-resolution mass spectrometry as well as the fragmentation pattern. Of 12 test UGT enzymes, only four (UGT1A1, 1A3, 2B4, and 2B7) showed metabolic activities toward belinostat. UGT1A1 was the most active enzyme, followed by UGT2B7, 1A3, and 2B4. Kinetic profiles for UGT1A1, 1A3, 2B4, and 2B7 were well described by Michaelis–Menten, Michaelis–Menten, Hill equation, and substrate inhibition equation, respectively. 4. Glucuronidation of belinostat was markedly inhibited by emodin and apigenin (two potent inhibitors of UGT1A1), and by quinidine and diclofenac sodium (two selective inhibitors of UGT2B7). Belinostat glucuronidation was found to be significantly correlated with β-estradiol 3-O-glucuronidation and zidovudine glucuronidation. 5. It was concluded that in addition to UGT1A1, UGT2B7 was also an important contributor to belinostat glucuronidation.